Ectomycorrhizal colonization of Alnus acuminata Kunth in northwestern Argentina in relation to season and soil parameters - Becerra, Alejandra Gabriela (2005)
The objective of this study was to determine patterns of ECM colonization of Andean alder at two natural forests in relation to soil parameters at two different seasons (autumn and spring). The soil parameters studied were field capacity, pH, electrical conductivity, available P, total N and organic matter. Twelve ECM morphotypes were found on A. acuminata roots. The ECM colonization varied among soil types and was affected positively by electrical conductivity. Multiple regression relationships among ECM colonization and edaphic properties variables showed no significant differences at two seasons and among soil types with respect to morphotype diversity values. Positive correlations were found between three morphotypes (Cortinarius tucumanensis, Gyrodon monticola and Russula alnijorrulensis) and soil types and two other morphotypes (Naucoria escharoides and Lactarius sp.) between two seasons. Results of this study provide evidence that ECM colonization of A. acuminata is affected by some chemical edaphic parameters and indicate that some ECM morphotypes are sensitive to changes in seasonality and soil parameters.